Clinicopathological Correlation of Prostate Malignancy with Serum Prostate-Specific Antigen (PSA) Levels and Radiological Imaging Findings - Sajid Ali Ahmad, Ghulam Mustafa, Rubina Shafi, Muhammad Atif Munawar, Rida Khan, Hamid Nawaz Khokhar (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Prostate cancer is one of the most prevalent malignancies affecting elderly men and remains a significant cause of cancer-related morbidity and mortality. Accurate diagnosis and assessment of tumor aggressiveness depend on a combination of biochemical markers, radiological imaging, and histopathological evaluation. Serum prostate-specific antigen (PSA) testing and imaging modalities such as transrectal ultrasound (TRUS) and multiparametric magnetic resonance imaging (mpMRI) are widely used in clinical practice; however, their diagnostic value is best understood when correlated with histopathological findings. Objective: To evaluate the clinicopathological correlation of serum PSA levels and radiological imaging findings with histopathological diagnosis and Gleason grading in patients with suspected prostate malignancy. Methods: This cross-sectional study was conducted from January 2023 to June 2023 at the Department of Urology, CMH Kharian Medical College, Kharian, Pakistan, in collaboration with Sughra Shafi Medical Hospital Complex. Seventy male patients aged 50 years and above with clinical suspicion of prostate malignancy were enrolled. Serum PSA levels were measured prior to biopsy. Radiological evaluation included TRUS for all patients, with mpMRI performed in selected cases. TRUS-guided prostate biopsy specimens were examined histopathologically and graded using the Gleason scoring system. Correlations between PSA levels, imaging findings, and histopathological outcomes were analyzed. Results: Prostate adenocarcinoma was confirmed in 65.7% of patients. Elevated PSA levels, particularly values greater than 10 ng/mL, and radiological findings suspicious for malignancy showed a strong association with biopsy-proven cancer and higher Gleason scores, indicating increased tumor aggressiveness. Conclusion: Serum PSA levels and radiological imaging findings demonstrate a significant clinicopathological correlation with prostate malignancy. Their combined assessment improves diagnostic accuracy and supports effective risk stratification and clinical decision-making. Keywords: Prostate cancer; Prostate-specific antigen; Transrectal ultrasound; Multiparametric MRI; Gleason score; Clinicopathological correlation.